Review Artikel: Tinjauan Aplikasi LC-MS/MS dalam Analisis Senyawa Alamiah dari Berbagai Sumber Daya Alam - Muhammad Fadhli; M. Chaidir Hafidz; Hidayatur Rizky; Luthfia Raisah Ahyati; Nor Hilalliyah; Regina Nabila; Sri Muliany (An-Najat, 2025)
This study provides a comprehensive review of the application of Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS) in the analysis of various natural product sources. LC-MS/MS has emerged as one of the most reliable and sensitive instrumental techniques for the identification, characterization, and quantification of bioactive compounds. Its strength lies in the ability to detect minute quantities of analytes, even in complex matrices such as plant extracts, microorganisms, and marine organisms. Numerous studies reviewed in this research demonstrate the effectiveness of LC-MS/MS in profiling chemical constituents from natural sources. Plants such as Allium ascalonicum L., Zingiber officinale, Uncaria sclerophylla, Momordica charantia L., Artocarpus integer, Garcinia xanthochymus, Piper nigrum Linn., Pometia pinnata, and Synsepalum dulcificum have been successfully analyzed using this method. Additionally, microorganisms like Aspergillus flavus and marine organisms such as Callyspongia aerizusa have also been studied with the same approach. The identified compounds belong to several major classes of secondary metabolites, including alkaloids, flavonoids, terpenoids, and saponins. These compounds have been reported to exhibit significant biological activities such as antioxidant, antidiabetic, anticancer, antimalarial, and enzyme-inhibiting properties. The successful identification and profiling of these bioactives provide a strong scientific foundation for the development of natural product-based innovations, including herbal medicines, health supplements, natural cosmetics, and functional foods. LC-MS/MS also plays a critical role in pharmacokinetic studies, method validation, and quality control of natural products. The advancement of data analysis software and improvements in instrument resolution have further strengthened the capability of LC-MS/MS to support multidisciplinary research based on biodiversity. In conclusion, LC-MS/MS is a key analytical tool that facilitates efficient and systematic exploration of bioactive compounds from nature. This review highlights the importance of integrating advanced technology in the sustainable utilization of natural resources to drive innovation in the health, industrial, and scientific research sectors.